Nationality Thought in Developing Critical Education - A. A. Gde Putera Semadi (Journal of Sustainable Development Science, 2021)
Critical education has a very strategic role in supporting and accelerating the formation of a civilized democratic society. Its existence is able to change the world, create the culture, carve out the history, engineer the world to be more fair and humane, even to change concepts, ideas, systematics, and strength. Implementation of critical education is based on three dimensions: the pedagogic practical, normative, and cultural ideology dimensions. Critical education process is formulated as a process of cultural dimension. The main function and target of critical education is "self-awareness", or "critical awareness". The concoction of Indonesian nationalism as a reflection of critical education has been clearly being pioneered since revolution era by R.A. Kartini, Budi Utomo, and K. H. Dewantara in the form of the establishment of some schools and the freedom of indigenous children to get the education. More qualified human resources can be cultivated through a critical education.